An Economic Appraisal of Small to Medium Scale Alluvial Gold Mining Systems in Papua New Guinea (The Australasian Institute of Mining and Metallurgy, 1991)
The small scale alluvial gold mining industry in Papua New Guinea (PNG) is c.irrently the only form of small scale mining carried out in this country. It already contributes significantly to the economy with current production estimated at 2 000-2 500kg per year. Until recently, small scale alluvial gold mining has been confined to simple panning and sluicing of high grade alluvial and colluvial deposits. Traditionally the small scale miner in PNG has only worked gravels with gold grades in excess of 500mg/m3. Grades of this order are required to justify the hard physical labour involved ~n hand operated small scale mining methods. .he introduction of higher throughput technologies such as trommels fed by hydraulic excavators has the effect of altering what constitutes an economically viable deposit. Mechanised techniques allow for the consideration of grades of almost half that level. The potential and opportunities for utilising this type of small scale mechanised mining in PNG are enormous with large areas of ground with gold grades running in excess of 250mg/m3 and often up to 2000mg/m3 throughout the country. An assessment of the current operating economics of this technology in the PNG context is the principal objective of this paper. Small to medium scale mechanised mining can potentially contribute significantly to the PNG economy particularly as it lies within the react-, of many PNG businessmen. Its potential is currently somewhat limited by a general lack of infrastructure and is also constrained by socio-political factors.